Sustainable Innovations in Green Nanotechnology for Nanoparticle Synthesis - Oluwanifemi (International Journal of Photochemistry and Photochemical Research, 2025)
Green nanotechnology is an emerging field that focuses on the environmentally friendly production of nanoparticles through biological and sustainable processes. This approach has diverse applications across industries such as pharmaceuticals, energy, electronics, and bioengineering. Compared to conventional methods, biologically driven nanoparticle synthesis, particularly utilizing green chemistry principles, offers a safer, eco- friendly, non-toxic, and cost-effective alternative. Metal nanoparticles are commonly synthesized through top-down and bottom-up strategies using physical, chemical, and biological methodologies. Characterization techniques such as UV- Vis spectrophotometry, Fourier-transform infrared spectroscopy (FT-IR), scanning electron microscopy (SEM), transmission electron microscopy (TEM), X-ray diffraction (XRD), atomic force microscopy (AFM), and other advanced analytical tools confirm nanoparticle properties. This review highlights the synthesis, characterization, and applications of biologically synthesized metal nanoparticles, particularly silver, gold, iron, selenium, and copper, emphasizing their biomedical and environmental advantages.
Keywords: Biological nanoparticle synthesis; Biomedical and environmental applications; Characterization techniques; Green nanotechnology; metal nanoparticles